Towards an Ideal Tafsir Methodology and Sayyid Mawdudi's Tafhimul Qur`an - Noor Mohammad Osmani; Md Habibur Rahman; Md Yousuf Ali (Faculty of Qur’an and Sunnah,Islamic College University of Perlis, 2024)
Non-Indexed Publication